Effectiveness of Corporate Governance Practices in Islamic Banks: An exploratory Study - Aasi, Mada (2009)
With the increasing importance of Islamic finance worldwide, the issues related to corporate governance also started to capture the attention of industry practitioners as well as researchers. The corporate governance related issues in Islamic banks stem from the unique relationship between the bank and investment account holders, specifically unrestricted investment accounts holders. Addressing these issues and investigating how effective are the current employed corporate governance practices in Islamic bank, is the main objective which this study is trying to achieve. Assessment would be carried out on eight full-fledge Islamic banks in four different countries; Bahrain, Kuwait, Malaysia and United Arab Emirates. After analysing the collected data and conducting the assessment of the selected banks, general themes and patterns would emerge reflecting the real situation concerning the corporate governance practices. Evaluating these practices would enable drawing general conclusion on how Islamic banks are dealing with the corporate governance issues resulting from their relationship with unrestricted investment holders, and how effectives are such practices in avoiding any agency problems.